Implementation of CERDIK Model on the Knowledge Level of Adolescents About Hypertension Prevention in pandemic Area of East Telukjambe Center of Public Health (PUSKESMAS) Karawang Regency in 2021 - erlena, erlena (J I K O (Jurnal Ilmiah Keperawatan Orthopedi), 2022)
One of the problems that contributed to the largest numbers of mortality and maternal morbidity was anemia during the postpartum period. It is estimated that 50-80% of women suffer from anemia 48 hours after birth. Anemia in women is associated with increased birth Infant Low Birth Weight (LBW), prematurity, maternal and child deaths, and infections. This study aims to identify the relationship between dietary patterns and the incidence of iron deficiency anemia in post Partum mothers at dr. Zainoel Abidin hospital Banda Aceh. This research is a quantitative study with a cross-sectional study design. This research was conducted from June to September 2019 with 102 respondents selected through the non-probability sampling method. Respondents were postpartum mothers who were treated in room 2 (obstetric inpatient room). The study technique was carried out by giving a questionnaire and a hemoglobin check has been carried out using an HB meter.  The data obtained were analyzed using the chi-square statistical test with a confidence level of 95%. This study found that the prevalence of anemia was  49,0% of respondents had mild anemia (Hb levels 9-10,9 gr/dl), 10,8% had moderate anemia (Hb levels 7-8,9 gr/dl), and 40,2% not having anemia (Hb levels >11gr / dl). Overall, there is a significant relationship between dietary patterns and the incidence of anemia in postpartum mothers at dr. Zainoel Abidin Banda Aceh (p-value 0,032).